Analisis Keberlanjutan Program Pelatihan Pemanfaatan Teknologi Bagi Guru Di Era Post Pandemic - Mauludin, Iqwan; Nadifa, Milatun; Akhmad, Khabib Fauzi; Setiawan, Khoirul Andri; Arifin, Imron; Ubaidillah, Aan Fardani (Universitas Negeri Malang, 2024)
Abstract : The development of Information and Communication Technology (ICT) has transformed the education landscape, expanding the scope of the teaching and learning process beyond the traditional classroom. Although the utilization of technology in education brings many benefits, there are still challenges in ensuring that teachers have the necessary skills and knowledge to use it effectively. This research aims to analyze the sustainability of technology utilization training programs for teachers in post-pandemic era in terms of influencing factors and applicable strategies. The method used is a systematic literature review following the PRISMA guidelines. After analysis, 33 articles were found to be relevant to the topic. The results indicate that factors such as relevant training materials, trainer capabilities, and participant engagement play crucial roles. Recommended strategies include online-based approaches, hierarchical training, and the formation of teacher communities. The roles of school principals, educational departments, and school communities are also crucial in supporting the sustainability of training programs. Thus, collaboration between various parties and the implementation of appropriate strategies are key in maintaining the sustainability of technology utilization training programs for teachers in the post-pandemic era.Abstrak : Perkembangan teknologi informasi dan komunikasi (TIK) telah mengubah lanskap pendidikan, memperluas cakupan proses belajar mengajar di luar ruang kelas tradisional. Meskipun pemanfaatan teknologi dalam pendidikan membawa banyak manfaat, masih ada tantangan dalam memastikan bahwa guru memiliki kemampuan dan pengetahuan yang cukup untuk menggunakannya secara efektif. Penelitian ini bertujuan untuk menganalisis keberlanjutan program pelatihan pemanfaatan teknologi bagi guru di era post pandemic dari segi faktor-faktor yang mempengaruhinya dan strategi yang dapat diterapkan. Metode yang digunakan systematic literature review dengan mengacu pada pedoman PRISMA. Setelah dianalisis terdapat 33 artikel menjadi pokok bahasan yang sesuai. Hasilnya menunjukkan bahwa faktor-faktor seperti materi pelatihan yang relevan, kemampuan pelatih, dan keterlibatan peserta pelatihan berperan penting. Strategi yang disarankan antara lain pendekatan berbasis online, pelatihan berjenjang, dan pembentukan komunitas guru. Peran kepala sekolah, dinas pendidikan, dan komunitas sekolah juga krusial dalam mendukung keberlanjutan program pelatihan. Dengan demikian, kolaborasi antar berbagai pihak dan penerapan strategi yang tepat menjadi kunci dalam menjaga keberlanjutan program pelatihan pemanfaatan teknologi bagi guru di era post pandemic.